2016
DOI: 10.1021/acsami.6b10314
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Oxide Stacked Electron Transport Layer for Highly Efficient Inverted Quantum-Dot Light Emitting Diodes

Abstract: We report highly efficient inverted quantum-dot light emitting diodes (QLEDs) using an Al doped ZnO (AZO)/Li doped ZnO (LZO) stack electron transport layer (ETL). An introduction of the LZO layer on AZO improved the current and power efficiencies of the green (G-) QLEDs from 10.5 to 34.0 cd A and from 5.4 to 29.6 lm W, respectively. The red (R-), G-, and blue (B-) QLEDs fabricated in this work exhibited the maximum external quantum efficiencies (EQEs) of 8.4, 12.5, and 4.3%, respectively. It is found from time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…The structure of control device is an ITO/PEDOT:PSS (30 nm)/PVK (15 nm)/green QDs/Li doped ZnO (LZO) (70 nm)/Al (100 nm). The CdSe/CdS/ZnS green QDs are used for the EML . The PVK and LZO are chosen as the HTL and electron transport layer (ETL), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of control device is an ITO/PEDOT:PSS (30 nm)/PVK (15 nm)/green QDs/Li doped ZnO (LZO) (70 nm)/Al (100 nm). The CdSe/CdS/ZnS green QDs are used for the EML . The PVK and LZO are chosen as the HTL and electron transport layer (ETL), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They found that decreasing the particle sizes led to ZnO ETLs with higher effective electron mobility and devices with lower turn‐on voltage and higher efficiency. Jang and co‐workers employed a bi‐layered ETLs consisting of Li‐doped ZnO (LZO) and Al‐doped ZnO . The authors suggested that the LZO layer improved electron injection and decreased exciton loss at the interfaces of QD/oxide.…”
Section: Prototype Qledsmentioning
confidence: 99%
“…N-type oxide is an ideal electron transport material and p-type oxide is used as hole injection material for QLEDs. [8][9][10][11] The oxide n-p CGJ is expected to efficiently generate and inject charges to the bottom and top QLEDs under forward bias. 1) The voltage at luminance of 1 cd m -2 .…”
Section: Resultsmentioning
confidence: 99%